ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS - Amartani, Pingky Ria; hendro, Su; Dewi, Riana (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
The purpose of this study was to test the empirical analysis of the factors affecting bank profitability (ROA) case study at Banks registered on the Indonesian stock exchange with independent variable income component, that are loan interest income, credit provision income, fee based income, and components costs consist of the cost of gifts and assurance, cost PPAP, NIM, ROA, LDR and NPL in 2014-2017period.. The analysis used  multiple linear regression analysis to test the hypothesis simultaneously using statistical test F whereas partial hypothesis test using t statistical test. he analysis showed that variable loan interest income, credit provision fee, fee based income, the cost of gifts and assurance, cost PPAP, NIM, ROA, LDR and NPL simultaneously significantly affect the bank's profitability (ROA) level of significance 5 %. While partial variable loan interest income not significant and negative, credit provision income and fee based income effect is not significant and is positive, gifts and assurance fees not significant and negative, costs PPAP significant influence and be positive. As for the ratio of significant and positive impact NIM, ROA and LDR ratio is significant and negative effect, and the NPL ratio insignificant and negative againts the bank's profitability (ROA) at Banks. The predictive ability of independent variables on the dependent variable amounted to 91.9%, while 8.1% is explained by other factors outside the research model..